Changes in the structure and geography of tourist flows during the COVID-19 pandemic - Manakov A. G.; Krastev V. K.; Krasilnikova I. N.; Ivanov I. A. (Baltic Region, 2023)
Tourism suffered more than many other sectors amid Covid-19 travel restrictions. This article looks at the impact of the pandemic on the territorial redistribution of tourist flows in the Baltic region. The study draws on regional annual and monthly data on international and domestic tourist arrivals between 2019 and 2021, available on the websites of the statistical offices of the Baltic Region countries. The regions earlier dependent on tourist arrivals from Russia experienced the largest drop in inbound tourism during the Covid-19 pandemic. Yet, domestic tourism burgeoned in most of the region’s countries. In 2021, the most dramatic increase in domestic arrivals occurred, year on year, in the border regions of Russia’s Northwest Federal District; the growth was also notable in Finland and the Baltic States. Domestic tourist flow compensated, partially or even fully, for the decrease in inbound tourist flow in most regions. The structure of inbound tourism changed markedly during the pandemic, with the share of tourists from the Baltic States growing. The strongest rise was in some regions of southern Finland and more modest in Latvia and Lithuania.